The Effect of Sorbitol on the Mechanical Properties of Temu Ireng Rhizomes (Curcuma Aeruginosa Roxb.) Starch Biodegradable Plastic - Santy Meilisa Manurung; Erna Frida; Susilawati Susilawati; Syahrul Humaidi; Perdinand Sinuhaji (IKIP Mataram, 2023)
Biodegradable plastic is made by mixing from temu ireng rhizomes starch matrix, sorbitol as a plasticizer, and chitosan as a filler through the melt intercalation method. heating process at 800C and drying at 70oC. The results show that the addition of chitosan and sorbitol has an effect on the characteristics of the plastic. The best tensile strength results on biodegradable plastic with a mass composition of starch: chitosan 5:5 gram without the addition of sorbitol is 4.03 MPa. The best percentage of elongation in plastic with a composition of starch: chitosan 8:2 gr and 3 ml Sorbitol is 99.68%. The best water resistance to biodegradable plastic was the composition of starch: chitosan 5:5 gr without the addition of sorbitol is 83.33%. And the best biodegradability in plastic with a composition of 5:5 chitosan without the addition of sorbitol was 100% for 9 days. FTIR test results show that biodegradable plastic have the same wavelength as their constituent raw materials. This shows that the resulting film only interacts physically.